Municipal solid-waste recycling market and the European 2020 Horizon Strategy: A regional efficiency analysis in Spain. - Expósito-García, Alfonso; Velasco-Morente, Francisco (Elsevier, 2018)
This paper focuses on the analysis of the efficiency of Spanish regions in the development of the recycling market in their respective territories through the use of a novel Data Envelopment Analysis method with multiple outputs. The efficiency analysis takes into account the mandatory goals of reducing mixed-collected municipal solid waste and the augmentation of selective collection of recyclable materials, as set by the European Union and the Spanish legal framework. This issue is highly relevant, since neither of these two management goals may be achieved without the recycling market and its associated industry having been previously developed to a sufficient level. Results confirm that Catalonia, Navarre and Madrid function as benchmark regions to be emulated by the remaining inefficient regions. The necessary regional investments and output projections to reach an efficient development of the recycling sector are also estimated. Additionally, it is found that per capita income and population density significantly explain differences in regional efficiencies. Finally, taking efficient regions as benchmarks to learn from, some policy recommendations are offered.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/13808
Keywords: Residuos urbanos - Gestión; Residuos - Aprovechamiento; Municipal solid waste management; Waste recycling; Waste reduction; Recycling market; Spain